Parametric programming of CNC lathes - Vasilić Goran V.; Živanović Saša T.; Milutinović Milan D. (Tehnika)
Parametric programming of CNC machines belongs to advanced programming techniques that provide several advantages compared to the generally accepted ways of creating G-code programs. Until now, manufacturers of CNC machines and their control units have mostly used this way of programming to create fixed processing cycles. Despite the range of possibilities it provides, parametric programming is not sufficiently representative of the end users of CNC machines. CNC machine programmers do not use this way of programming due to insufficient training and a lack of literature for education. This paper presents the basics and principles of parametric programming of CNC machines. According to the explanations, a parametric program can be written for any CNC machine. The paper presents examples of parametric programs written for typical operations realized on a CNC lathe.